Electrophysiological correlates of morphological processing in Chinese compound word recognition - Du, Yingchun; Hu, Weiping; Fang, Zhuo; Zhang, John xuexin (Frontiers in Human Neuroscience, 2013)
The present study investigated the electrophysiological correlates of morphological processing in Chinese compound word reading using a delayed repetition priming paradigm. Participants were asked to passively view lists of two-character compound words containing prime-target pairs separated by a few items. In a Whole Word repetition condition, the prime and target were the same real words (e.g., 经理-经理, manager-manager). In a Constituent repetition condition, the prime and target were swapped in terms of their constituent position (e.g., 士护-护士, the former is a pseudo-word and the later means nurse). Two ERP components including N200 and N400 showed repetition effects. The N200 showed a negative shift upon repetition in the Whole Word condition but this effect was delayed for the Constituent condition. The N400 showed comparable amplitude reduction across the two priming conditions. The results reveal different aspects of morphological processing with an early stage associated with N200 and a late stage with N400. There was also a possibility that the N200 effect reflect general cognitive processing, i.e., the detection of low-probability stimuli.